Low back pain in adolescent female rowers and the associated factors - Perich, D.; Burnett, A.; O'Sullivan, P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
There were two aims of the current study; firstly, to determine the incidence of low back pain in adolescent female rowers and secondly, to determine the differences between LBP and no-LBP groups for a range of physical tests and psycho-social variables. The point prevalence of LBP was 47.5% for rowers and 15.5% for controls indicating that LBP is common in this group of rowers. When no-LBP and LBP groups were compared for the data collected in this study, LBP subjects showed significantly decreased lower limb endurance and back muscle endurance and sitting with more erect postures. Although this study cannot determine causation, it has the potential to direct interventions to decrease the incidence of LBP in this group.